Metrik Pemasaran Sebagai Alat Untuk Mengukur Kinerja Pemasaran Perusahaan (Studi Kasus Pada Bisnis Ritel) - James Rianto Situmorang (Jurnal Administrasi Bisnis, 2010)
Marketing activities as any other company functions such as finance, production,human resources should be measured if their performance meets the specified targetcompany. To measure the performance of companies used marketing tool known asa marketing metric. Marketing metrics that can be used or made available so muchso that the company should be able to choose the appropriate metric variation inaccordance with the standards set by the company and also the type of companybusiness. If the marketing performance meets the targets that have been defined, themarketing metrics can be associated with profitability and shareholder value.Keywords: Marketing metrics, brand metrics, customer metrics, marketing performance,value metrics, forward looking, retail